2010
DOI: 10.1183/09031936.00153209
|View full text |Cite
|
Sign up to set email alerts
|

Repaired oesophageal atresia: respiratory morbidity and pulmonary function in adults

Abstract: Although after oesophageal atresia (OA) repair in infancy, respiratory problems are common, their natural history remains unclear. We assessed morbidity, pulmonary function (PF), and bronchial hyperresponsiveness (BHR) in adults with repaired OA respiratory.588 patients who underwent surgery for OA during 1947-1985 were identified and those 262 who were alive and had their native oesophagus were included. Respiratory symptoms and respiratory symptom-related quality of life (RSRQoL) were assessed by questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(134 citation statements)
references
References 37 publications
8
121
0
5
Order By: Relevance
“…It also importantly examines the often ignored quality of life issues faced by this patient group. The large size of this study group makes it more representative of the wider international population of OA patients than most of the existing literature which is limited to smaller national [4,10] and institutional data series [3,7,13] or meta-analyses [8]. The study participants are broadly representative of the wider population based on anatomy of original defect in comparison to EUROCAT figures [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also importantly examines the often ignored quality of life issues faced by this patient group. The large size of this study group makes it more representative of the wider international population of OA patients than most of the existing literature which is limited to smaller national [4,10] and institutional data series [3,7,13] or meta-analyses [8]. The study participants are broadly representative of the wider population based on anatomy of original defect in comparison to EUROCAT figures [14].…”
Section: Discussionmentioning
confidence: 99%
“…How transition is managed in the future is an important issue for OA care and other chronic paediatric conditions, as the population of long term survivors continues to increase. International studies such as this alongside work from Australia [22], Finland [9,10] Holland [23,24] and more recently the USA [25] are key in highlighting the need for careful planning of patient centred transitional and adult care. This may include the need for some stratification of transition and follow up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent follow-up study of a large cohort of adult EA-TEF survivors revealed that 21% had restrictive respiratory disease, 21% had obstructive respiratory disease, and 36% had both ventilatory defects. In addition, 41% had bronchial hyperreactivity often consistent with asthma, and these patients had overall impaired respiratory quality of life in comparison with a group of age-matched controls (40). Postoperative rib fusions, scoliosis, and gastro-esophageal reflux were found to account in part for these respiratory sequelae, but other explanations are possible.…”
Section: Lung Hypoplasia In Esophageal Atresiamentioning
confidence: 88%
“…Patients may suffer apneic spells (72,73) or barking cough (74) during infancy and childhood, frequent vomiting (75), repeated pneumonia (69,76,77) and/or chronic respiratory tract disease (78) that are considered as sequelae of the esophageal malformation but that might be related directly to the GER. Recurrent anastomotic strictures are indeed related to GER and become manageable after effective anti-reflux treatment (79).…”
Section: The Problem Of Associated Gastroesophageal Reflux (Ger)mentioning
confidence: 99%